Climate Change Mitigation and Adaptation in Nepal and South Asia: Challenges, Progress, and Recommendations - Giri, Suja; Prabhakar, Aman; Malla, Rohit Babu; Oli, Sameeksha; Poudel, Sandip; Khanal, Ashish (Journal of Sustainability and Environmental Management, 2023)
This study examines the challenges and status of climate change mitigation and adaptation in South Asian countries, with a specific focus on Nepal. The study employs a purposive sampling approach, selecting countries based on the engagement of researchers in those regions and performing a comprehensive literature review. The analysis of the gathered literature provided valuable insights into the challenges of climate change mitigation and adaptation in South Asian countries, particularly Nepal. The study highlights the significant impacts of climate change on sectors such as agriculture, infrastructure, and coastal regions. However, it also acknowledges the progress made through the implementation of climate change mitigation and adaptation measures. Despite the progress, challenges remain in effectively addressing climate change, with current measures falling short of the ambitious targets set by the Sustainable Development Goals (SDGs) and the Paris Agreement. To address these challenges, the study recommends strengthening regional collaboration and knowledge sharing, prioritizing the adoption of renewable energy technologies, investing in climate-resilient infrastructure, promoting sustainable agricultural practices, developing comprehensive policy frameworks, exploring innovative financing mechanisms, and enhancing capacity and awareness.